2018
DOI: 10.3390/ijms19020404
|View full text |Cite
|
Sign up to set email alerts
|

Different Achilles Tendon Pathologies Show Distinct Histological and Molecular Characteristics

Abstract: Reasons for the development of chronic tendon pathologies are still under debate and more basic knowledge is needed about the different diseases. The aim of the present study was therefore to characterize different acute and chronic Achilles tendon disorders. Achilles tendon samples from patients with chronic tendinopathy (n = 7), chronic ruptures (n = 6), acute ruptures (n = 13), and intact tendons (n = 4) were analyzed. The histological score investigating pathological changes was significantly increased in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…The hierarchical structure with aligned collagen fibers was observed in both groups. The findings of the present study showed no signs of a degenerated tendon as the fibers were aligned and evidence of disorganization was not found [32][33][34]. Therefore, we conclude that axial compression of the tibia used in this study does not induce a degeneration process in the mouse Achilles tendon.…”
Section: Discussionsupporting
confidence: 39%
“…The hierarchical structure with aligned collagen fibers was observed in both groups. The findings of the present study showed no signs of a degenerated tendon as the fibers were aligned and evidence of disorganization was not found [32][33][34]. Therefore, we conclude that axial compression of the tibia used in this study does not induce a degeneration process in the mouse Achilles tendon.…”
Section: Discussionsupporting
confidence: 39%
“…Kannus et al found that, in most of the spontaneously ruptured tendons, the pathological changes via biopsy were degenerative such as hypoxic degenerative tendinopathy, mucoid degeneration, and tendolipomatosis [4]. Compared with the normal tendons, the fat metabolism and inflammatory cells of the tendons suffering from acute or chronic ruptures were detectable [23]. With the elastography technique, De Zordo et al found that a normal tendon was hard, and 57% of tendons with symptoms of tendinopathy showed marked softening [11].…”
Section: Discussionmentioning
confidence: 99%
“…The numerous micromorphological changes of tendinosis include decreased collagen density; disruption of collagen orientation and organization; increased sonographic hypoechogenicity; angiogenesis; and possible ingrowth of nerves (Riley, 2004;Cook and Purdam, 2008;Xu and Murrell, 2008;Klatte-Schulz et al, 2018). Although the tendinotic Achilles may show these changes at the myotendinous junction or insertion, they are most common in its mid-substance, where tendon thickening is localized (focal thickening).…”
Section: Morphological Considerations In Achilles Tendinosismentioning
confidence: 99%